2008
DOI: 10.1055/s-0031-1278299
|View full text |Cite
|
Sign up to set email alerts
|

Five-year treatment of chronic venous insufficiency with O-(β-hydroxyethyl)-rutosides: Safety aspects

Abstract: Chronic venous insufficiency (CVI), and related signs and symptoms of venous and diabetic microangiopathy, can be effectively treated with O-(β-hydroxyethyl)-rutosides (HR). The aim of the present independent registry study was to evaluate HR in a long-term (five-year) period of administration that examined the tolerability and safety of HR. Patients with severe CVI and venous microangiopathy were included in the registry. Subjects who completed five years of treatment were considered in the analysis. Blood pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
0
4
0
2
Order By: Relevance
“…The benchmark for authenticating rutin's neuroprotective properties is clinical trials in humans. A few clinical trials have been conducted to examine the effect of a compound from the rutin family, O-( β -hydroxyethyl)-rutosides (HRs) in venous disease patients with diabetes treated for a prolonged period of time [ 211 ]. HRs is obtained by substituting rutin hydroxyl groups with O- β -hydroxyethyl groups.…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…The benchmark for authenticating rutin's neuroprotective properties is clinical trials in humans. A few clinical trials have been conducted to examine the effect of a compound from the rutin family, O-( β -hydroxyethyl)-rutosides (HRs) in venous disease patients with diabetes treated for a prolonged period of time [ 211 ]. HRs is obtained by substituting rutin hydroxyl groups with O- β -hydroxyethyl groups.…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
“…HRs is obtained by substituting rutin hydroxyl groups with O- β -hydroxyethyl groups. Human clinical trials with rutin (in the form of HRs) have shown that it is safe and well tolerated [ 211 ]. The lack of clinical trials exploring the efficacy of rutin in NDs is of concern.…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
“…Согласно национальным и международным клиническим руководствам, применение комбинированных флеботонических препаратов позволяет повысить эффективность терапии и снизить риски рецидива заболевания [17][18][19][20][21][22]. Значимость флеботропных препаратов в лечении хронической венозной недостаточности достаточно изучена, что позволяет их широко использовать в симптоматической терапии, в то время как эффективность флеботонических препаратов в лечение геморроя до сих пор обсуждается, несмотря на имеющиеся результаты проведенных исследований [23][24][25][26][27][28][29]. Флеботропные препараты повышают тонус венозной стенки, благоприятно влияют на микроциркуляцию, улучшают венозный кровоток и лимфатический дренаж за счет увеличения частоты и амплитуды перистальтики лимфатических сосудов, купируют воспалительные реакции за счет подавления адгезии лейкоцитов к эндотелию, препятствуя их миграции в перивазальное пространство и блокируя выброс цитокинов и протеолитических энзимов [20,30,31].…”
Section: в статье представлены результаты консервативной терапии пациunclassified
“…In seven human studies submitted, the effect of different flavonoids (diosmin and beta-hydroxyethylrutosides, beta-hydroxyethyl-rutosides, diosmin and hesperidin, and micronised purified flavanoid fraction (MPFF) consisting of diosmin and hesperidin), on symptoms of chronic venous disease was evaluated (Jantet, 2000;Belcaro et al, 2002;Danielsson et al, 2002;Jantet et al, 2002;Cesarone et al, 2006;Belcaro et al, 2008;Stuard et al, 2008). Other studies were related to pharmacokinetic EFSA Journal 2014;12(1):3511 aspects (Kienzler et al, 2002;Kanaze et al, 2007) and the methods of detection of flavonoids in the human body (Spanakis et al, 2008) and did not address the effects of the food which is the subject of the claim.…”
Section: Scientific Substantiation Of the Claimed Effectmentioning
confidence: 99%